A competitividade no mercado transoceânico de pelotas de minério de ferro, seus delineadores e o posicionamento dos integrantes deste mercado - Virgilio Costante Gaggiato (2010)
The mining companies located in the main iron ore producing countries, Brazil, Australia, India, South Africa, Ukraine, Russia, China, USA and Canada dominate the world´s production and have being enjoying extremely favourable conditions in their relationship with the steel industry, responsible for around 99% of the world´s demandfor iron ore. However, aspects such as quality, logistics and advantages related to the production cost which will be able to be translated into lower prices for better margins for the supplier, have been holding a remarkable place in the composition of the competitive differential amongst the companies of this business sector. This newtransoceanic iron ore market set up has created new typical conditions in order to determine the competitiveness of the sector and to define which party will be stronger to serve the future demand. In this way, this paper has developed a taxonomy applied to the evaluation of thecompetitiveness of the companies who act in the transoceanic iron ore segment, focused mainly in the pellets market, analyzing in general the historic aspects and trends of this market through competitiveness analysis´ models applicable to this sector. It was attested that due to the high returns of the mining sector in the last years, the barriers to new entrants such as the needs of economy of scale, of capital and theconstraint of distribution channels have been mitigated by the increased attraction of the sector. Many projects are already in course and there exists a concrete pressure towards a supply increase in the next years. This brings impacts to the sector gains and stirs its competitiveness. However, due to the fact that the current players in the market still enjoy high profit margins and faces a condition of excess demand, theintensity of the competition within the sector is low. Even with the outlook of changes in the competitiveness scenario for this sector, it is relevant to highlight that the iron ore and steel market present cyclic characteristics being applicable a possibility that in the near future the current unfavorable scenario to the steel industry be repeated.